Identification of Maternity Mothers with Uterine Inertia at the Kendari City Regional General Hospital - Adryani Mujur (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
Uterine inertia is a uterine abnormality in which there is insufficient strength to open the cervix or push the fetus out. The causes of uterine inertia are his abnormalities, emotional factors and strength, misdirected labor, abnormal location of the CPD, disturbances in the formation of the uterus during the embryonic period, wrong administration of oxytocin and sedative drugs, excessive stretching of the uterus in multiple pregnancies or hydramnios, and postmature pregnancy. The effects of uterine inertia are prolonged labor, exhaustion, dehydration, and intrapartum infections. To Identify Maternity Mothers With Inertia Uteri at the General Hospital of Kendari City. This type of research implemented in June 2022 at General Hospital Kendari city. the study population was all women with maternal inertia in General Hospital kendari city with a total of 37 ceses. the sampling technique is total sampling.the type of data is quantitative data the data source of research is secondary data. The mother's age, 27 cases occurred at the age of 20-35 years and a few cases occurred at the age of > 35 because of 8 cases. for maternal parity, there was a lot of parity I as many as 14 cases and a few cases in > IV parity of 5 cases. for maternal education, it mostly occurred in SMP as many as 15 cases and a little occurred in DIII / SI as many as 3 cases. for maternal occupation, it occurred mostly in IRT as many as 26 cases and a little occurred in self-employed as many as 3 cases